Pengaruh Faktor Fisik Rumah Adat Suku Dawan terhadap Kejadian ISPA pada Bayi (Di Desa Obesi dan Neonbesi Kec. Mollo Utara Kab. Timor Tengah Selatan Propinsi Nusa Tenggara Timur) - Junias, Marylin; Budiyono, Budiyono (Jurnal Kesehatan Lingkungan Indonesia, 2004)
ABSTRACT Background : The highest incident of ARI is at North Mollo district, at Kapan Public Health Center. There where 51 cases of ARI-Pnemonia in babies (26%) and 189 cases for the last two months (February-March 2004). In a humid tropical environment, living in a traditional house Ume kbubu is a suitable choice, especially during the rainy season, because the people there feel warm. The traditional house of Dawan triad Ume kbubu has unique arsitecture, but it is far from being healthy house. Besides the unfavorable extrinsic and intrinsic factor of the traditional house of the Dawan Ume kbubu can be a predisposition of an incident ARI cases on babies. Methods: This research is observational research with cross sectional approach for analyzed the effect of physical factor’s of traditional house Dawan triad on the baby’s ISPA cases. This research take place at Obesi and Neonbesi village,Kec. Mollo Utara,Kab. TTS, Propinsi NTT. The total responden is 60 baby’s mother. 21 of them living in the traditional house ume kbubu, is the sample and for the equal sample is 39 who live in the non traditional house. Resulst: There is significant difference between physical traditional house and non traditional house with the baby;s ISPA cases, as following humidity , temperature ,Population Density and long of living. To test the relationship between the physical factor of the traditional house of the Ume kbubu and the incident of ARI (Annual Rate Incidende) in babies , using multiple logistic regresition test, α = 0,05 and it has a significant result that is population density and  temperature Conclusions : Based on that result we conclude that there is significant difference between physical traditional house and non traditional house with the baby;s ISPA cases. Keyword : incident of ARI in babies, environmental factors.